2015
DOI: 10.1093/ehjci/jev314
|View full text |Cite
|
Sign up to set email alerts
|

Elongation of chordae tendineae as an adaptive process to reduce mitral regurgitation in functional mitral regurgitation

Abstract: Our results suggest the posterior leaflet chords possibly remodel by elongating and contribute to reduced MR and that in a subgroup of FMR patients, the primary chords may remodel by shortening, resulting in augmented MR. This information could be useful in choosing strategy for FMR correction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 24 publications
1
32
0
Order By: Relevance
“…Papillary muscle (PM) displacement due to left ventricular (LV) remodeling results in leaflet tethering that restricts valve closure. Ischemic MR also reflects a mismatch between valve and ventricular size as the damaged heart enlarges but the MV fails to keep pace (29). Stiffening and fibrosis further limit valve closure (1012).…”
Section: Introductionmentioning
confidence: 99%
“…Papillary muscle (PM) displacement due to left ventricular (LV) remodeling results in leaflet tethering that restricts valve closure. Ischemic MR also reflects a mismatch between valve and ventricular size as the damaged heart enlarges but the MV fails to keep pace (29). Stiffening and fibrosis further limit valve closure (1012).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, patients with dilated cardiomyopathy and moderate or severe MR showed unbalanced remodeling, such as short leaflets and short chordae tendinae. A correlation between chordal length and IMR development has also been suggested by others 18,19 . In general, it was demonstrated that the leaflet area increases in patients with chronic IMR, but leaflet adaptation does not seem to be adequate in patients with significant IMR 20,21 .…”
Section: Discussionmentioning
confidence: 57%
“…Activation of TGF‐β can be favorable, but, if enhanced by angiotensin II receptor activation, it can induce fibrotic changes in the MV, as described by Grande‐Allen et al, 13 eliminating the possibility of augmenting the valvular area. The second‐order chords are subjected to the same mechanisms 19 . If MV adaptation is balanced, IMR grade can be absent of mild even in the presence of a large heart.…”
Section: Discussionmentioning
confidence: 99%
“…Such chordal cutting reduces both MR and its associated LV remodelling 13 and has been successfully applied by several surgical groups. 14 -16 The pathological changes observed in chordae post-infarction 7 and the recent reported relation between secondary MR and chordal shortening, imposing additional restriction on the tethered leaflets, lend further support to the potential benefits of chordal cutting to relieve such MR. 17 The current paper reports a proof of concept for using pulsed cavitational focused ultrasound (histotripsy) to cut chordae non-invasively guided by real-time 3D echocardiography. 3 The authors show that secondary anterior chordae can be selectively cut in vitro and in vivo in the beating sheep heart with a high-energy Figure 1 (A) Functional/ischaemic MR: the PM is displaced posteriorly, laterally, and apically because of local LV dilatation and remodelling (arrows) caused by MI (shaded area).…”
mentioning
confidence: 99%
“…Three-dimensional transoesophageal echocardiography may offer improved guidance. 17 (iv) Application of cavitational focused ultrasound will need to be achieved without thoracotomy. Optimally, a transoesophageal or gastric window may prove to be sufficient.…”
mentioning
confidence: 99%